2021
DOI: 10.3390/molecules26123665
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effect of Polyphenolic-Rich Fractions of Corn Silk on Protecting Endothelial Cells against High Glucose Damage Using In Vitro and In Vivo Approaches

Abstract: Endothelial cell dysfunction is considered to be one of the major causes of vascular complications in diabetes. Polyphenols are known as potent antioxidants that can contribute to the prevention of diabetes. Corn silk has been reported to contain polyphenols and has been used in folk medicine in China for the treatment of diabetes. The present study aims to investigate the potential protective role of the phenolic-rich fraction of corn silk (PRF) against injuries to vascular endothelial cells under high glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…[96] Besides, the phenolic-rich fraction of CS protects the endothelial layer from high glucose by restoring cell viability dose-dependent manner and preventing histological changes in the aorta of STZinduced rats. [97] Hence, in vivo or in vitro studies, CS polysaccharides exhibited anti-diabetic effects, and total flavonoids, water extract, methanol extract, 95 % EtOH extract, and the phenolic-rich fraction of CS were also critical contributors to anti-diabetic activities.…”
Section: Anti-diabetic Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…[96] Besides, the phenolic-rich fraction of CS protects the endothelial layer from high glucose by restoring cell viability dose-dependent manner and preventing histological changes in the aorta of STZinduced rats. [97] Hence, in vivo or in vitro studies, CS polysaccharides exhibited anti-diabetic effects, and total flavonoids, water extract, methanol extract, 95 % EtOH extract, and the phenolic-rich fraction of CS were also critical contributors to anti-diabetic activities.…”
Section: Anti-diabetic Effectmentioning
confidence: 99%
“…The results showed that both 300 mg/kg and 500 mg/kg CSFs have significantly reduced weight loss, water consumption, and especially blood glucose concentration in diabetic mice, suggesting that CSFs have a potential therapeutic effect on diabetes [96] . Besides, the phenolic‐rich fraction of CS protects the endothelial layer from high glucose by restoring cell viability dose‐dependent manner and preventing histological changes in the aorta of STZ‐induced rats [97] . Hence, in vivo or in vitro studies, CS polysaccharides exhibited anti‐diabetic effects, and total flavonoids, water extract, methanol extract, 95 %EtOH extract, and the phenolic‐rich fraction of CS were also critical contributors to anti‐diabetic activities.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Протективный эффект КСР исследовали in vitro с использованием эндотелиальных клеток пупочной вены человека, а в последствии in vivo у крыс с диабетом, индуцированным стрептозоцином. Показано, что фенольная фракция КСР может оказывать положительный эффект на пациентов с диабетом и играть значимую роль в предотвращении развития и прогрессирования диабетических осложнений, таких как диабетическая нефропатия и атеросклероз [46].…”
Section: гипогликемическое и антидиабетическое действиеunclassified
“…Corn silk, the dried style and stigma of Zea mays L., is a wellknown traditional Chinese medicine which has been widely used as tea [1,2], herb medicine [3][4][5], and food ingredients [6,7]. Corn silk contains rich favonoids [5,8,9], polysaccharides [10,11], and terpenoids [12,13], which possess a variety of biological activities including antioxidant [9], hypoglycemic [6,14], anticancer [4,15], and antibacterial properties [16][17][18].…”
Section: Introductionmentioning
confidence: 99%